ANALYSIS OF STRESSED AND DEFORMED STATE AND CALCULATIONS ON STRENGTH AND STIFFNESS OF RING PLATES UNDER VARIOUS BOUNDARY CONDITIONS - Зеленський, Анатолій; Баранчикова, Діана (SWorldJournal, 2025)
Section 1 substantiates the importance of studying ring plates during bending for understanding the qualitative and quantitative nature of the change in the stress-strain state (SSS) according to the classical theory. Section 2 indicates the goal: analyti